2018
DOI: 10.1159/000494533
|View full text |Cite|
|
Sign up to set email alerts
|

CXCR4 Accelerates Osteoclastogenesis Induced by Non-Small Cell Lung Carcinoma Cells Through Self-Potentiation and VCAM1 Secretion

Abstract: Background/Aims: Non-small cell lung carcinoma (NSCLC) metastasis to bone leads to skeletal-related events and a poor quality of life. Unravelling the mechanism of metastasis is crucial for improving survival. Previous work has implicated the role of CXCR4 in bone metastasis; however, the underlying mechanisms are unknown. Methods: The human bone metastasis tissue samples were obtained from lung cancer patients during surgery with consents. The patients were followed up and the overall survival curve was analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…Thus, research on mechanisms about how NSCLC bone metastases occur has been a hot spot in recent years. LncRNA MALAT1, miRNA-33, CXCR4, and TGF-β signaling have all been reported to contribute to bone metastases of NSCLC (Liu et al, 2016;Popper, 2016;Liao et al, 2018;Yang et al, 2019). Interestingly, in our present work, we firstly report that PNMA5 enhances NSCLC bone metastases as a target gene of BMP2 signaling.…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…Thus, research on mechanisms about how NSCLC bone metastases occur has been a hot spot in recent years. LncRNA MALAT1, miRNA-33, CXCR4, and TGF-β signaling have all been reported to contribute to bone metastases of NSCLC (Liu et al, 2016;Popper, 2016;Liao et al, 2018;Yang et al, 2019). Interestingly, in our present work, we firstly report that PNMA5 enhances NSCLC bone metastases as a target gene of BMP2 signaling.…”
Section: Discussionsupporting
confidence: 44%
“…The gene expression changes of NSCLC cells can mediate the secreting factors of NSCLC cells, which subsequently regulate the osteoclast differentiation. High expression of CXCR4 in NSCLC cells have been shown to promote cancer cells-mediated osteoclast differentiation through secreting VCAM1 (Liao et al, 2018). Moreover, C5aR1 can also enhance NSCLC cells to induce osteoclast differentiation through secreting CXCL16 (Ajona et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, the NSCLC-derived exosomes produce amphiregulin which induces EGFR pathway activation in pre-osteoclasts, consequently causing increased expression of receptor activator of nuclear factor-kappa-Β ligand (RANKL), associated with the vicious cycle in osteolytic bone metastasis [ 74 ]. Lung tumor-derived exosomal induction of osteoclastogenesis is also linked with factors such as acceleration by C-X-C chemokine receptor type 4 (CXCR4) through self-potentiation and vascular cell adhesion molecule 1 (VCAM1) secretion [ 75 ], differential expression of the RANKL/RANK/OPG system [ 76 ], and activation of the EGF pathway by multiple myeloma-derived exosomes enriched in amphiregulin in the bone microenvironment [ 77 ]. Sequencing of plasma-derived exosomal miRNAs of lung cancer patients revealed three consensus clusters that showed significant differential expression.…”
Section: Exosomes and Lung Cancer Metastasismentioning
confidence: 99%
“…In addition, it was marginally correlated with brain metastasis (p=0.068) and lymph node metastasis (p=0.085), as well as worse OS (p=0.004) and PFS (p=0.005). Liao et al (122) Tumor tissue…”
Section: C-mesenchymal-epithelial Transitionmentioning
confidence: 99%
“…Recent findings indicated that CXCR4 expression on tumor cells plays a positive role in key downstream pathways, including PI3K/AKT/mechanistic target of rapamycin kinase (PI3K/AKT/MTOR) and extracellular signal-regulated kinase 1/2 (ERK1/2), which promote tumor proliferation and migration (149). Vascular cell adhesion molecule 1 (VCAM1) was also shown to be an activator of CXCR4, with ADAM metallopeptidase domain 17 (ADAM17) as a downstream mediator (122). Zuo et al (150) demonstrated that overexpression of CXCR4 enhanced cell motility and invasion via EGFR and matrix metallopeptidase 9 (MMP9), owing to the positive correlation among them.…”
Section: C5a (Cd88)/ C5armentioning
confidence: 99%